Pengaruh Lifestyle Brand Ambassador Product Quality terhadap Purchase Decision Pada Produk Skincare Whitelab - Fitria Sheva Yulianti; Tirton Nefianto (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2023)
In the era of progress in the field of knowledge and technology, industries in the world are experiencing developments. One of them is in the beauty industry. Currently skincare is so popular that it makes the beauty industry grow very rapidly. Skincare is one of the treatments carried out by teenagers to adults to maintain their appearance. With this phenomenon, there is industrial competition that spurs companies to mutually improve product quality, as well as the quality of their companies. The purpose of this study is to identify the influence of lifestyle, product quality, brand ambassadors on purchase decisions simultaneously or partially, then identify the dominant variables in influencing purchase decisions. The sample in this study amounted to 200 respondents with a minimum sample 150 respondents. Data collection technique using purposive sampling. Then the data is processed using multiple linear regression method using SPSS. Based on the test results, it is known that lifestyle, brand ambassador, product quality variables simultaneously and partially have a positive effect on purchase decisions. The product quality variable has a positive but not dominant effect on purchase decisions. Furthermore, the results show that the Lifestyle variable is the most dominant variable in influencing purchase decisions.